РЕАКЦІЯ АНТИТІЛ КЛАСУ IgG НА ІНФЕКЦІЮ SARS-CoV-2 - Кузьмінов, Б. П.; Мажак, К. Д.; Ткач, О. А.; Щурко, Г. В.; Зарічна, О. З. (Українські медичні вісті, 2023)
РЕАКЦІЯ АНТИТІЛ КЛАСУ IgG НА ІНФЕКЦІЮ SARS-CoV-2